Project-Based Learning in Smart Solar Panel System for Analysis 21st Century Skills - Ihtiari Prastyaningrum; Pramudya Ardi; Endhah Purwandari; Wahyu Hidayat (Jurnal Penelitian Pendidikan IPA, 2024)
Collaboration and communication are two types of 21st-century skills that are very important for students to have. By having good communication and collaboration skills, students can build a wider network in the future, which is useful to support their lives. Students' communication and collaboration skills can be known through various activities, one of which is the involvement of students in project-based learning. The purpose of this study is to determine the effect of a modified project-based learning model on students' collaboration and communication skills. The project-based learning that we did focused on the project of making a smart solar system. This research is a type of development research, with a mixed method research method. We developed a modified project-based learning model. The data collection process was carried out by conducting in-depth interviews, and in-depth observations, supported by literature studies. In addition, we also used a measurement questionnaire to provide a numerical assessment of students' collaboration and communication skills. Based on the research conducted, we found that the modified project-based learning model can be used to determine the extent of students' communication and collaboration skills. Where the measurement results show good criteria in some indicators and sufficient on several other indicators.